2020
DOI: 10.3390/antiox9070617
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-Erythroid 2-Related Factor 2 (Nrf2) and Mitochondrial Dynamics/Mitophagy in Neurological Diseases

Abstract: Mitochondria play an essential role in bioenergetics and respiratory functions for cell viability through numerous biochemical processes. To maintain mitochondria quality control and homeostasis, mitochondrial morphologies change rapidly in response to external insults and changes in metabolic status through fusion and fission (so called mitochondrial dynamics). Furthermore, damaged mitochondria are removed via a selective autophagosomal process, referred to as mitophagy. Although mitochondria are one of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 117 publications
(269 reference statements)
2
49
0
Order By: Relevance
“…In contrast to mitochondrial fission (Zhou et al, 2018b;Wang et al, 2020c), fusion is associated with a drop in the number of mitochondria but an increase in the quality of mitochondria. It must take place before damaged mitochondria can be repaired by a healthy mitochondrion (Kang, 2020;Wang et al, 2020,d). Fusion is also necessary for the exchange of metabolic substrates between two mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to mitochondrial fission (Zhou et al, 2018b;Wang et al, 2020c), fusion is associated with a drop in the number of mitochondria but an increase in the quality of mitochondria. It must take place before damaged mitochondria can be repaired by a healthy mitochondrion (Kang, 2020;Wang et al, 2020,d). Fusion is also necessary for the exchange of metabolic substrates between two mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are known as one of the primary sources of cellular ROS production. Nrf2 signaling is observed to counteract the mitochondria-derived ROS [ 44 ]. Its mechanism is summarized as the following three aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is known to be a redox-sensitive transcription factor which induces antioxidant and detoxifying enzymes in order to protect cells from oxidative stress [ 81 ]. It has shown that Nrf2 activation is able to suppress mitochondrial oxidative stress and is beneficial for suppressing disease pathology including epilepsy [ 16 ].…”
Section: Mitochondrially Targeted Antioxidants As Neuroprotective mentioning
confidence: 99%